Is private school premium spurious?: the role of private schools in the Philippines - Yamauchi, Futoshi; Abrenica, Joy (Asian Development Bank, 2003)
This paper examines schooling investments and the returns in private and public schools in the Philippines, using data from a recent employee survey. The purpose of this paper is to identify the sources of rerturn premiums in private school education. Some findings are highlighted: i) the premium in returns to elementary education in private schools is significant for production workers, while ii) the return premium to high school education in private schools is significant for non-production workers. However, iii) these premiums are in fact spurious in that private schools screen out better students, which augments earnings through positive correlation between private school enrollment and higher earning endowment. Therefore, although private institutions are dominant in the country, investments in private school education do not increase productivity of agents through human capital accumulation, but select more potentially productive agents before entering labor markets. Wether or not this type of selection mechanism through private schools is superior than public schools in developing countries depends on the benefit of early-stage signaling and the costs of education from both private and social viewpoints.